Change in the results of middle-distance runners living at different heights above sea level - Shesterova, L. Y.; Yefremenko, A. N.; Apaichev, A. V.; Samolenko, T. V.; Maslyak, I. P.; Tu, Y.; Perevoznik, V. I.; Krajnik, Y. B. (Journal of Physical Education and Sport, 2018)
Purpose: to study the dynamics of the results of the competitive activity of runners at 1500 m, living in a plain and in a mountainous area, in a year-long preparation cycle. Material and methods. Study involved 20 qualified middle-distance runners, which were divided into two groups. The first group consisted of 10 runners at 1500 m, mainly living in the plain, the second group consisted of 10 runners at 1500 m, mainly living in the mountainous area. Athletes who took part in the experiment, trained according to one program. In the course of the research, the following methods were used: analysis and generalization of literary sources, experiment, analysis of competition protocols, methods of mathematical statistics. Results: the dynamics of the results of runners at 1500 m, living at different heights above sea level; revealed the positive effect of training in the middle altitude on the athletic result; time frame for showing the best results are established. Conclusions: 1. Analysis and generalization of the literature sources showed insufficient study of the dynamics of the sports results of runners at 1500 m, reside at different altitudes above sea level. 2. Obtained data indicate that runners living on the plain show higher and stable results during the competition period than athletes living in highlands. 3. Analysis of competitive activities showed that runners at 1500 m, living on the plain, the best results are shown on the 4th day after descent from the mountains, and athletes living in the highlands - on the 80th.